Causality Between Foreign Direct Investment and Economic Growth: a Comparative Study of India and China . - Kumar, Ganesh (2011)
In the last three decades, Foreign Direct Investment flows have grown rapidly all over the world. This is because many developing countries see FDI as an important element in their strategy for economic development. The FDI has both benefits and costs and its impact is determined by the country‟s specific condition in general and the policy environment in particular. It is a fact that FDI is one of the most effective ways by which developing economies are integrated with the rest of the world, as it provides not only capital but also a medium of acquiring skills, technology, organizational and managerial practices and access to markets. The relationship between FDI and economic growth is very controversial; it varies from country to country and even within a country in different time periods. Since the early 1990s the world has witnessed rapid economic transformation and growth in India and China. This has subsequently triggered a boom in comparative studies of the two Asian giants. The basic objective of this paper is to investigate the causality between economic growth and FDI in India and China. To examine the same, we employed “The Granger Causality Test”.